LET'S PROTECT BAYAD BREED SHEEP FROM PASTERELLIS DISEASE (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
In Karakul farming, especially among sheep and lambs, the death of sheep and lambs as a result of the spread of pasteurellosis in natural conditions is causing great damage to the economy of many Karakul farmers. Therefore, it is necessary to protect Bayad sheep imported from Mongolia from pasteurellosis. As a result of these diseases among sheep, the mortality rate of sheep is 30-70%. This article provides a detailed description of the development of pasteurellosis pathogens, epizootological data, clinical signs, pathomorphological changes in each organ, methods of diagnosis, treatment, prevention and control.